Integrasi Nilai Akhlak dalam Pembelajaran Pendidikan Agama Islam Berbasis Media Digital - Mujib, Ahmad; Subando, Joko (Lembaga Yasin AlSys, 2026)
The development of digital technology has brought significant changes to instructional practices in Islamic Religious Education (PAI), on the one hand opening up opportunities for interactive and contextual learning innovation, but on the other hand presenting challenges in the form of potential moral degradation among students. This article aims to examine the integration of akhlak values into PAI learning based on digital media through a literature review approach. The method used is library research by analyzing various scholarly sources in the form of books, journal articles, and relevant educational policy documents. The findings show that the integration of akhlak values in PAI learning using digital media can be carried out through value-oriented instructional planning, the selection of ethical and educational digital media, teachers’ role modelling in technology use, and the strengthening of reflection and habituation of commendable attitudes in learning activities. With such an approach, digital media function not only as a means of delivering content, but also as an effective vehicle for character formation and the cultivation of akhlak among students in the digital era.